Are young fathers "hard to reach"? Understanding the importance of relationship building and service sustainability. Issue 4 (19th December 2016) - Davies, Laura
Abstract : Purpose: This paper explores service provision for young fathers through analysis of data from the three-year ESRC funded project Following Young Fathers. The purpose of this paper is to explore the idea that young fathers are a "hard to reach" group. It begins with a discussion of literature and research evidence on this theme. The empirical discussion draws on data collected in interviews and focus groups with practitioners, service managers and those working to develop and deliver family support services. Design/methodology/approach: The ESRC Following Young Fathers study used qualitative longitudinal methods to research the perspectives of fathers under the age of 25, mapping the availability of services to support them and investigating professional and policy responses to their needs. The strand reported on here focussed on the perspectives of a range of practitioners, service managers and those involved in developing and commissioning services. Findings: The research findings, and those of other projects discussed in the paper, challenge the idea that young fathers are "hard to reach", suggesting that we should, conversely, consider that many services are actually hard to access. Thus, increasing young fathers' engagement requires better understanding of their often complex needs and a reshaping of service design and delivery to account for them. The paper highlights how the configuration, funding and delivery of services can inhibit young fathers' use of them, and identifies ways in which they could be made more accessible. Originality/value: The ESRC Following Young Fathers Study filled an important gap in knowledge about the lives of young fathers, developing understandings of their experiences and support needs. The strand reported on here draws on research with practitioners to provide an in-depth discussion of how services currently support young fathers, and how they could be better configured to address their often complex and diverse needs.